A series of pure-blue-light emitting Cu(i) complexes with thermally activated delayed fluorescence: structural, photophysical, and computational studies. Issue 5 (3rd January 2017) - Huang, Chun-Hua; Wen, Meng; Wang, Chun-Ya; Lu, Yong-Feng; Huang, Xi-He; Li, Hao-Hong; Wu, Shu-Ting; Zhuang, Nai-Feng; Hu, Xiao-Lin
Abstract : Four Cu(i ) complexes exhibiting pure blue delayed fluorescence were synthesized and their structures and photophysical properties were studied. Abstract : Four mononuclear Cu(i )–halide complexes containing phosphines and pyridine ligands with strong electron donor substituents, [CuCl(PPh3 )2 (4-NMe2 py)] (1 ), [CuI(PPh3 )2 (4-NH2 py)] (2 ), [CuI(POP)(4-NH2 py)] (3 ), and [CuI(POP)(4-NMe2 py)]·0.5(Et2 O) (4 ), (PPh3 = triphenylphosphine, 4-NMe2 py = 4-(dimethylamino)pyridine, POP = bis[(2-diphenyl-phosphino)phenyl]ether, 4-NH2 py = 4-aminopyridine, Et2 O = diethyl ether) were synthesized and studied with regard to their structural, photophysical properties and theoretical calculations. The complexes exhibit pure blue thermally activated delayed fluorescence ( λ max = 442 (1 ), 436 (2 ), 464 (3 ), and 448 nm (4 )) in crystalline at room temperature. Emission lifetime analyses and density functional theory (DFT) calculations show that the blue-light emission at room temperature is the singlet (metal + halide)-to-ligand charge transfer state, ( 1 (M + X)LCT), while that at 77 K is the state of 3 (M + X)LCT transition character, owing to the small singlet–triplet energy gaps (Δ E = 660–1680 cm −1 ). X-ray diffraction structure analysis, photophysical studies and theoretical calculations suggest that the much larger torsion angle between the N-heterocyclic rings and N–Cu–X planes of complex3 than that of1, 2 and4 might causes the bathochromic shift of luminescence, although these complexes containing similar heterocycle ligands.